ПОЛИМЕТАМОРФИЗМ В КОЛЬСКИХ БЕЛОМОРИДАХ И ПРОБЛЕМЫ ПЕГМАТИТО- И РУДОГЕНЕЗА (РИКОЛАТВИНСКОЕ ПЕГМАТИТОВОЕ ПОЛЕ) - Гродницкий Л.Л.; Крохин А.И.; Инина И.С. (My University, 1989)
Geological, PT and geochemical conditions of evolution processes for regional metamorphism, metasomatism and resulted pegmatite and ore genesis related the general tectonic and plutonic region development are considered on the basis of complex studies of the large pegmatite field, theKola part of belomorides. Three metamorphis stages are distinguished: the main (rebolsky), ore (svekokarelsky) and rost-ore. It is shown that the main features of metamorphic ore system discretely developing in time are determined by the dimensional localization of ascendental crust fluids, temperature reducing, theirs base activity, increasing of water activity and at the last stage of cardon dioxide at the relatively constant high pressure. Distinctive features of this object coparing to metamorphic ore system of Kola part of Belomorsky belt consist in the high activity of alkalies (mainly of K and Rb) in fluid resulted in variations of composition of pegmatites and ores.
Keywords: ПОЛИМЕТАМОРФИЗМ; МЕТАМОРФИЗМ; БИОТИТЫ; ГРАНИТНЫЕ ПЕГМАТИТЫ; МЕТАСОМАТИЗМ; 553.2.06:552.4(=924.16)